Changes of the colon and rational choice of drug for treatment of chronic constipation in senile patients - S. G. Burkov; E. V. Kasimtseva; L. Yu. Agafonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Clinical and endoscopical investigation of the large intestine in patients of senile age with chronic constipation and estimation of rational treatment.Material and methods. Overall 287 senile patients with chronic constipation were included in original study (mean age 79±2,7). Complex investigation included videocolonoscopy and choosing of drug for rational therapy.Results. It was revealed, that digestive and endocrine diseases are most common in this group of patients. At endoscopic investigation diverticulosis and polyposis coli were the most frequent findings. All patients have tolerated investigation well, no complications have developed. Restoration of regular defecations on a background of lactulose (Duphalac) intake was accompanied by disappearance of feeling of incomplete defecation and necessity of intensive straining effort at defecation.Conclusions. In senile patients chronic constipation is widespread functional disorder, which does not exclude, however, endoscopic control. The age of the patient is not a limiting factor for colonoscopy. Lactulose (Duphalac) is an optimal pharmaceutical with high efficacy.